Conducting neuromarketing studies ethically-practitioner perspectives - David Hensel; Ana Iorga; Lisa Wolter; Judith Znanewitz (Cogent Psychology, 2017)
Understanding consumer behavior has always been a marketer’s goal. No wonder that, with the emergence of consumer neuroscience, which promised to shed light into what made consumers tick, companies were attracted to this new field. A major downside of this promising field is that especially commercial studies have struggled in the past with ethical issues. This may be the effect of less transparent ethical standards in the business world compared to academia. The potential of neuromarketing can only be exploited effectively, if trust in the industry rises and this correlates strongly with ethical behavior. Therefore, guidelines for conducting ethical neuromarketing studies have already emerged, but have not been evaluated from a practitioner perspective so far. Hence, the aim of this study is first to check the validity of additionally developed ethical aspects that are supplementary to the NMSBA (Neuromarketing Science & Business Association) code of ethics, contained in the EGNM (Ethical Guideline in Neuromarketing) guideline by determining whether there is a consensus with the answers provided by neuromarketing practitioners. The second objective is to refine the ethical guideline with additional aspects which are relevant for practitioners. Interview data, collected from 10 neuromarketing practitioners, showed that all seven aspects are important when conducting neuromarketing studies. Furthermore, the results indicate five additional ethical aspects that should be considered.